Optimization of reduced graphene oxide (RGO) coating process as a pre-treatment to enhance activity of palladium catalyst for electroless plating - Chong, Jian Rong (2019)
This study uses reduced graphene oxide (rGO) to form a conductive nanofilm on a non-conducting substrate to investigate its effects on enhancement of low catalyst loading electroless nickel plating (ENP). Graphene oxide reduction methods were optimized in this study and the properties of electroless nickel plating were analysed along with the reduced graphene oxide film. The experiments conducted in the study includes an rGO coating process, a catalysing process using palladium chloride (II) solution, and a ENP process. The basic design of this study was to compare ENP characteristics between 2 sets of samples, one control set with no rGO pre-treatment, and one experimental set with rGO pre-treatment. 3 major factors were used in the analysis of the effectiveness of rGO on enhancing ENP, namely sheet resistance of the substrate, ENP results, and catalyst loading on the substrate. Using various wet chemical reducing agents, indication of the successful reduction of graphene oxide (GO) onto a non-conductive ABS substrate was done by measuring the sheet resistance of the resultant nanofilm coating with a 4-point probe tester. An inductively coupled plasma mass spectrometer (ICP-MS) was used to characterise the catalyst loading on samples after ENP. Analysis of the results found that rGO is effective on improving the catalytic activity of low Pd loading ENP by 140%. Positive correlation between a lower sheet resistance and higher incidences of excellent ENP characteristics had also been found, thus concluding the enhancement of low catalyst loading ENP on non-conductive materials via application of rGO.